UNC50 prompts G1/S transition and proliferation in HCC by regulation of epidermal growth factor receptor trafficking. - Zhou Fang; Linuo Zhou; Songmin Jiang; Lihuan Cao; Long Yu (PLoS ONE, 2015)
UNC50 has long been recognized as a Golgi apparatus protein in yeast, and is involved in nicotinic receptor trafficking in Caenorhabditis elegans, but little is known about UNC50 gene function in human biology despite it being conserved from yeast to high eukaryotes.We investigated the relation between UNC50 and human hepatocellular carcinoma (HCC) and the potential mechanisms underlying HCC development.UNC50 mRNA expression patterns in 12 HCC and adjacent non-cancerous tissues determined using northern blotting were confirmed by real-time PCR in another 44 paired tissues. Microarray experiments were used to screen for global effects of UNC50 knockdown in the Hep3B cell line, and were confirmed by real-time PCR, western blotting, flow cytometry, and tetrazolium assay in both UNC50 overexpression and knockdown Hep3B cells.UNC50 expression levels were upregulated in HCC tissues in comparison with the adjacent non-cancerous tissues. UNC50 knockdown reduced mRNA levels of the downstream targets of the epidermal growth factor receptor (EGFR) pathway: cyclin D1 (CCND1), EGF, matrix metalloproteinase-7 (MMP7), aldose reductase-like 1 (AKR1B10), cell surface-associated mucin 1 (MUC1), and gastrin (GAST). Moreover, UNC50 influenced EGF, inducing cell cycle entry by affecting cell surface EGFR amounts.UNC50 may plays some roles in HCC progression by affecting the EGFR pathway.